The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jcm10204758
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Bleeding in Patients with SARS-CoV-2 Infection Managed by Interventional Radiology

Abstract: Background: This study was conducted to evaluate the technical and clinical success of trans-arterial embolization (TAE) as a treatment of gastrointestinal bleeding (GIB) in Coronavirus Disease 2019 (COVID-19) patients and to describe its safety; moreover, we describe the characteristics of these patients. Methods: Thirty-four COVID-19 hospitalized patients presented with GIB. Risk factors, drugs administered for COVID-19 infection, and clinical and biological parameters were evaluated. Furthermore, intraproce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…An element that could have hindered the rapid establishment of the diagnosis in this case was severe bleeding in a patient with a coagulopathy (a prolonged APTT and normal INR) and a history of major surgery without severe bleeding [ 34 ]. In our case, each bleeding episode was severe, resulting in severe anemia [ 35 ], but without hypovolemic shock, which contrasts with data obtained from other studies [ 36 , 37 ]. Coagulation tests, performed few days after admission, found a low level of FVIII, and a normal level of Factor IX.…”
Section: Discussioncontrasting
confidence: 99%
“…An element that could have hindered the rapid establishment of the diagnosis in this case was severe bleeding in a patient with a coagulopathy (a prolonged APTT and normal INR) and a history of major surgery without severe bleeding [ 34 ]. In our case, each bleeding episode was severe, resulting in severe anemia [ 35 ], but without hypovolemic shock, which contrasts with data obtained from other studies [ 36 , 37 ]. Coagulation tests, performed few days after admission, found a low level of FVIII, and a normal level of Factor IX.…”
Section: Discussioncontrasting
confidence: 99%
“…Several complications can arise during ICU stay, from both COVID-19 extensive lung damage and extra-pulmonary involvement, as well as those secondary to mechanical supporting systems [ 2 , 3 , 4 , 5 , 6 ]. Among these, bacterial and fungal co-infections and superinfections (or secondary infections) play an important role in COVID-19 disease and have been associated with increased morbidity and mortality, especially in critically ill patients [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as previously stated, in addition to systemic inflammation, liver dysfunction could be partially mediated by COVID-19-related coagulopathy and intrahepatic microvascular thrombosis [ 89 , 90 , 91 ]. This theory is also supported by laboratory findings, as demonstrated by a recent study that found an independent association between higher D-dimer levels and elevation of ALT [ 92 ].…”
Section: Hepatic Manifestations In Covid-19 Patientsmentioning
confidence: 85%